2014
DOI: 10.1186/1472-6882-14-459
|View full text |Cite
|
Sign up to set email alerts
|

The effect and underlying mechanism of Timosaponin B-II on RGC-5 necroptosis induced by hydrogen peroxide

Abstract: BackgroundNecroptosis is an important mode of cell death, which is due to oxidant stress accumulation. Our previous study indicated that oxidant stresses could be reduced by Timosaponin B-II (TBII), a kind of Chinese herb RhizomaAnemarrhenae monomer extraction. We wonder the possible effect of Timosaponin B-II, whether it can protect cells from necroptosis via reducing the oxidant stress, in RGC-5 following hydrogen peroxide (H2O2) insult.MethodsRGC-5 cells were grown in DMEM, the model group was exposed in H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Dysregulation of regulated necrosis contributes to the development of diseases, such as cancer, and neurodegeneration ( Galluzzi et al, 2014 ; Pasparakis and Vandenabeele, 2015 ). Although regulated necrosis includes several cell death types, such as, receptor interacting protein 3-dependent necroptosis that can be triggered by tumor necrosis factor-α ( Degterev et al, 2008 ; Jiang et al, 2014 ), erastin-induced ferroptosis that requires iron, mitochondrial permeability transition dependent regulated necrosis, etc. ( Gao et al, 2015 ; Kong et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of regulated necrosis contributes to the development of diseases, such as cancer, and neurodegeneration ( Galluzzi et al, 2014 ; Pasparakis and Vandenabeele, 2015 ). Although regulated necrosis includes several cell death types, such as, receptor interacting protein 3-dependent necroptosis that can be triggered by tumor necrosis factor-α ( Degterev et al, 2008 ; Jiang et al, 2014 ), erastin-induced ferroptosis that requires iron, mitochondrial permeability transition dependent regulated necrosis, etc. ( Gao et al, 2015 ; Kong et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rosenbaum et al [ 6 ] found a number of necroptotic cells in the rat retinal ganglion cell layer at 6 h after aHIOP. Our previous studies also indicated that necroptosis occurred in RGC-5 cells at an early stage following elevated hydrostatic pressure in vitro [ 15 ] or 300 μM hydrogen peroxide (H 2 O 2 ) treatment [ 14 ]. Recently, in vitro models of OGD have been widely applied to simulate neuronal ischemia in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Son et al [ 13 ] showed that Nec-1 can significantly reduce ROS production in Theiler’s murine encephalomyelitis virus (TMEV)-infected macrophages. Our previous studies showed that Timosaponin B-II, an anti-oxidative monomer extracted from Rhizoma anemarrhenae , reduced retinal ganglion cell-5 (RGC-5) cell necroptosis by inhibiting ROS accumulation [ 14 ]. Together, these results suggested that ROS accumulation might directly lead to necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…It is extracted from Anemarrhena asphodeloides rhizome and shows a very good antioxidant effect (Feng, Chen, Lin, & Liu, ). Many studies have shown that timosaponin BII not only has an effect on scavenging oxygen free radicals, and that it can inhibit the secretion of inflammatory cytokines and shows an obvious anti‐inflammatory effect (Jiang et al, ; Kim et al, ). In addition, T. J. Li, Qiu, Yang, Rui, and Chen () found that timosaponin BII can aid repair of impairment of learning and memory caused by cerebral ischemia through anti‐oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…BII not only has an effect on scavenging oxygen free radicals, and that it can inhibit the secretion of inflammatory cytokines and shows an obvious anti-inflammatory effect (Jiang et al, 2014;Kim et al, 2009). In addition, T. J.…”
mentioning
confidence: 99%